Identifikasi Faktor-Faktor Penyebab Gangguan Jiwa pada Remaja di Rumah Sakit Jiwa - Hidayat, Muhammad -; Hesty, Hesty -; Indrawati, Iin Indrawati -; Suri, Martha - (Jurnal Akademika Baiturrahim Jambi, 2024)
Adolescents (15-24 years) have a depression percentage of 6.2%. Severe depression will result in a tendency to harm oneself (self harm) and even commit suicide. Depression in teenagers can be caused by several things such as pressure in the academic field, bullying, family factors, and economic problems. This research aims to determine the factors that cause mental disorders in adolescents at the Jambi Province Mental Hospital, a type of retrospective descriptive study research. The results of the research showed that respondents based on gender provided information that 649 of the 846 teenagers were male (76.7%). Respondents based on age provided information that 660 of 846 teenagers were in their middle teens (78%). Respondents based on adolescent age provided information that 794 of 846 adolescents (94%) were diagnosed with psychotic mental disorders, schizophrenia and the best disorders F20 – F29 (schizophrenia, schizotypal disorders and delusional disorders). Respondents based on early adolescent age provided information that 132 of 143 early adolescent males (92.3%) were diagnosed with psychotic mental disorders, schizophrenia and the best disorders F20 – F29 (schizophrenia, schizotypal disorder and delusional disorder). Respondents based on middle adolescent age provided information that 466 out of 506 male middle adolescents (92.09%) were diagnosed with psychotic mental disorders, schizophrenia and the best disorders F20 – F29 (schizophrenia, schizotypal disorder and delusional disorder). It can be concluded that respondents based on adolescent age provided information that 794 out of 846 adolescents (94%) were diagnosed with psychotic mental disorders, schizophrenia and the best disorders F20 – F29 (schizophrenia, schizotypal disorders and delusional disorders).